EFEKTIVITAS HIDROTERAPI MANDI UAP PADA IBU NIFAS TERHADAP INVOLUSI UTERI DI POSKESDES PEDEKIK: PENDAHULUAN, METODE, PEMBAHASAN, KESIMPULAN, SARAN - Aisyah, Siti; Yanti, Rifa; Mardiya, Rizka (Universitas Muhammadiyah Surabaya, 2025)
Objective: The purpose of this study was to examine how steam baths impact uterine involution in primiparous mothers. Methods: This study used a quantitative method with a quasi-experimental design: Pretest and Posttest with Control Group Design. In this study, the researcher used a purposive sampling technique, meaning the researcher selected a sample of 30 primiparous mothers. The sample was then divided into three treatment groups, each with ten people. The first group received a standard steam bath without aromatherapy, and the second group received a standard steam bath with aromatherapy, and the second group received a traditional steam bath with aromatherapy. The Chi-square statistical test was used to analyze the data to determine differences in uterine involution among the three groups. Results: The results showed that the p-value on the first day after the intervention was 0.000; on the fourth day, it was 0.001; and on the eighth day, it returned to 0.000. There was a significant difference between the three groups in terms of uterine fundal height, as all values were less than α = 0.05. However, the analysis of lochia changes yielded different results. On the second day, the p-value was 1.000; on the seventh day, the p-value was 0.399; and on the fourteenth day, the p-value returned to 1.000. There was no significant difference between the three groups in terms of lochia changes, as all values were greater than α = 0.05. Conclusion: steam bathing significantly reduced uterine fundal height, but did not affect lochia changes in postpartum mothers.